Integrated management of root rot of sesamum caused by Macrophomina phaseolina (Tassi) Goid.: Integrated management of root rot of sesamum caused by Macrophomina phaseolina (Tassi) Goid. - T KIRAN BABU; T SHOBHA RANI; D PADMAJA (Journal of Oilseeds Research, 2020)
Integrated treatment viz., seed treatment with Trichoderma viride + Pseudomonas fluorescens @ 5 g/kg each + soil application of P. fluorescens @ 2.5 kg/ha + T. viride @ 2.5 kg/ha enriched in FYM + neem cake @ 250 kg/ha at the time of sowing resulted in minimum root rot incidence (13.0 %) and maximum percent reduction of disease over control (68.8%) and yield (304 kg/ha).